2021
DOI: 10.3390/app11052000
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring of 2D Plane Structures

Abstract: This paper presents the application of the observability technique for the structural system identification of 2D models. Unlike previous applications of this method, unknown variables appear both in the numerator and the denominator of the stiffness matrix system, making the problem non-linear and impossible to solve. To fill this gap, new changes in variables are proposed to linearize the system of equations. In addition, to illustrate the application of the proposed procedure into the observability method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Lin et al [16] developed a new fiber beam element (FBE) model that applies to both small and large CFT and slender columns. Finally, attention should also be directed towards exploring new solutions and approaches, including innovative materials and sustainable solutions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [16] developed a new fiber beam element (FBE) model that applies to both small and large CFT and slender columns. Finally, attention should also be directed towards exploring new solutions and approaches, including innovative materials and sustainable solutions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…V. Ducman et al detected changes in porosity in systematic foams by X-CT tomography to assess the effect on their macroscopic properties [14]. Behnam Mobaraki et al proposed an algorithm for an observability analysis of two-dimensional cellular structures, which provides a new approach for applications in characterizing concrete structures [15]. Studies on the preparation of foam concrete have shown that its density grade ranges from 300 to −1700 kg/m 3 and that its porosity is between 0.1 and 0.9 [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Building monitoring has become a matter of concern for engineers and architects as structures and building envelopes should meet the safety, habitability, and sustainability requests during the service life [1,2]. Accordingly, engineers decided to control performance of the buildings by monitoring two main parameters: (1) Structural parameters: in terms of structural system identification (SSI), some numerical approaches have been developed for inferring mechanical parameters of structures modeled with 1D elements (such as steel and concrete buildings, cable stayed bridges, trusses, and frames) [3][4][5], 2D elements (such as tunnels, culverts, and dams) [6], and 3D elements [7]. In terms of deriving parameters of structures modeled with 3D elements, various approaches have been presented in the literature [8,9].…”
Section: Introductionmentioning
confidence: 99%